2005
DOI: 10.1086/425961
|View full text |Cite
|
Sign up to set email alerts
|

Complex X‐Ray Absorption and the Fe Kα Profile in NGC 3516

Abstract: We present data from simultaneous Chandra, XMM-Newton, and BeppoSAX observations of the Seyfert 1 galaxy NGC 3516, taken during 2001 April and November. We have investigated the nature of the very flat observed X-ray spectrum. Chandra grating data show the presence of X-ray absorption lines, revealing two distinct components of the absorbing gas, one that is consistent with our previous model of a UV/ X-ray absorber while the other, which is outflowing at a velocity of $1100 km s À1 , has a larger column densi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
111
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 72 publications
(132 citation statements)
references
References 56 publications
20
111
1
Order By: Relevance
“…It is clear that the other layers of lower ξ gas may exist along the same sight-line but at larger radial distances from the central source: the highest-ξ zone could not exist outside the other gas layers as shielding would prevent it achieving log ξ > ∼ 4. Similar models have been discussed for sources such as e.g., NGC 3516 (Turner et al 2005) and NGC 4151 ) and thus it seems that spectral variations driven by a time-variable disk wind may be applicable across the Seyfert population.…”
Section: Discussionsupporting
confidence: 58%
“…It is clear that the other layers of lower ξ gas may exist along the same sight-line but at larger radial distances from the central source: the highest-ξ zone could not exist outside the other gas layers as shielding would prevent it achieving log ξ > ∼ 4. Similar models have been discussed for sources such as e.g., NGC 3516 (Turner et al 2005) and NGC 4151 ) and thus it seems that spectral variations driven by a time-variable disk wind may be applicable across the Seyfert population.…”
Section: Discussionsupporting
confidence: 58%
“…The highest velocity zone, at v r ∼ −0.02c, in which H-and He-like Fe lines form, is too highly ionized to produce detectable UV lines and, in fact, no UV absorption is detected at this velocity. And, as we have found in previous studies (e.g., Turner et al 2005), no lines are detected from the high-ionization, high-column, partial-covering zone. For the remaining zones, we list the model parameters, with U given for the equivalent ξ , and possible associated UV components, in Table 6.…”
Section: Connection With the X-ray Absorberssupporting
confidence: 84%
“…Coupled with their relatively high values of U, one consequence of the low column densities is that none of the three strongest components are sufficiently optically thick to the ionization radiation to justify including the effects of screening by intervening absorbers, e.g., as is the case in NGC 3516 (Kraemer et al 2002;Turner et al 2005) and NGC 4151 (Kraemer et al 2001(Kraemer et al , 2006. Also, while, as noted in Section 3, the continuum and BLR emission is reddened, consistent with an intervening column of N H = 1.0 × 10 21 cm −2 of dusty gas, none of the models for the UV absorber components have a sufficient column den- sity to account for the reddening.…”
Section: Model Resultsmentioning
confidence: 99%
“…NGC 3516: the detection of narrow highly ionized absorption features in the Chandra HETG and XMM-Newton EPIC pn spectra of this source have already been published by Turner et al (2005) and Turner et al (2008). In particular, the authors reported the presence of H/He-line resonant absorption lines from Mg, Si, S and Fe.…”
Section: Appendix B: Notes On Single Sourcesmentioning
confidence: 82%